DAMPAK KEHADIRAN JEMAAT GLORYA TUATUKA BAGI MASYARAKAT SEKITARNYA - Yuda D. Hawu Haba; Maria R. A. Pada (Phronesis: Jurnal Teologi dan Misi, 2022)
This research aims to know the context of the GMIT Glorya Tuatuka Congregation and its presence from 1941 to 2021. The method used in this research is a qualitative method with a historical approach. From this research, the following results were obtained: GMIT Glorya Tuatuka congregation, in its history, has reached the age of 80 years on 19 September 2021. This congregation is located in Tuatuka Village, East Kupang, Kupang Regency, East Nusa Tenggara. From the context of the Tuatuka Village, it became a place where members of the GMIT Glorya Tuatuka Congregation grew and developed. The GMIT Glorya Tuatuka congregation has been around for 80 years. This congregation was founded on 19 September 2021. At that time, Rev. H. Haning baptized 25 members of the Tuatuka congregation. This congregation initially worshipped at Babau, then to Mukeana (Kefetoran Am Abi Oefeto), to Gunoedale/Tuatuka Lama, and established a new fellowship in Tuatuka (Laku). Since its founding in the 1970s – today, this congregation has been served by eight Pastors. Thus, for 80 years, members of the GMIT Glorya Tuatuaka Congregation have been served by 16 pastors. Members of this congregation started with 37 family heads, and now there are 224 family heads. Its presence has an impact on the fields of ecclesiastical spirituality, socio-economics, politics, education, customs, and culture.